The Implementation of al-Ijarah al-Mausufah fi al-Zimmah in Umrah Travel - Almurni, Muhammad Furqon; Mukhlas, Oyo Sunaryo; Hakim, Atang Abd (Al-Mustashfa: Jurnal Penelitian Hukum Ekonomi Syariah, 2024)
The purpose of this research is to understand the application of al-ijÄrah al-maá¹£Å«fah fi al-Å¼immah (IMFZ) in Umrah travel. This research is particularly interesting due to the gap between the expectations of Umrah travel service users and the actual services provided by travel agencies. It is hoped that the standards proposed by the researcher will become the benchmark and monitoring mechanism for the Ministry of Religious Affairs in granting permits for Umrah travel agencies, thereby preventing fraud. The research method employed is descriptive analytical, which involves describing the contract law of IMFZ, analyzing the fiqh adaptation (takyÄ«f fiqh), and outlining the standards for IMFZ implementation in Umrah travel based on relevant research sources such as journals, books, and news. The results indicate that the application of IMFZ in Umrah travel must meet several standards. These standards include provisions related to services, payment conditions, as well as down payments and guarantees. All the aforementioned provisions refer to the DSN MUI Fatwa No. 101 concerning the IMFZ agreement.Keywords: al-ijÄrah al- mauá¹£Å«fah fi al-Å¼immah, takyiÄ«f al-fiqh and Umrah travel